The ultor-group of the genus Dolichogenidea Viereck (Hymenoptera, Braconidae, Microgastrinae) from China with the descriptions of thirty-nine new species - Liu, Zhen; He, Jun-Hua; Chen, Xue-Xin; Gupta, Ankita; Moghaddam, Mostafa Ghafouri (Zootaxa, 2019)
The ultor-group of the genus Dolichogenidea Viereck from China is revised, which totally 67 species are recorded. Thirty-nine new species are described and illustrated, i.e., D. alophogaster Liu & Chen, sp. nov.; D. altithoracica Liu & Chen, sp. nov.; D. anterocava Liu & Chen, sp. nov.; D. apicurvus Liu & Chen, sp. nov.; D. atarsi Liu & Chen, sp. nov.; D. breviattenuata Liu & Chen, sp. nov.; D. carborugosa Liu & Chen, sp. nov.; D. clausa Liu & Chen, sp. nov.; D. conpuncta Liu & Chen, sp. nov.; D. crassa Liu & Chen, sp. nov.; D. cucurbita Liu & Chen, sp. nov.; D. excellentis Liu & Chen, sp. nov.; D. flexitergita Liu & Chen, sp. nov.; D. fluctisulcus Liu & Chen, sp. nov.; D. flexisulcus Liu & Chen, sp. nov.; D. gleditsia Liu & Chen, sp. nov.; D. hemituba Liu & Chen, sp. nov.; D. hexagona Liu & Chen, sp. nov.; D. infirmus Liu & Chen, sp. nov.; D. latitergita Liu & Chen, sp. nov.; D. lincostulata Liu & Chen, sp. nov.; D. lobesia Liu & Chen, sp. nov.; D. longialba Liu & Chen, sp. nov.; D. longimagna Liu & Chen, sp. nov.; D. lunatus Liu & Chen, sp. nov.; D. medicava Liu & Chen, sp. nov.; D. minuscula Liu & Chen, sp. nov.; D. multicolor Liu & Chen, sp. nov.; D. obsoleta Liu & Chen, sp. nov.; D. opacifinis Liu & Chen, sp. nov.; D. ovata Liu & Chen, sp. nov.; D. parallodorsum Liu & Chen, sp. nov.; D. pentgona Liu & Chen, sp. nov.; D. punctipila Liu & Chen, sp. nov.; D. rectivena Liu & Chen, sp. nov.; D. transcarinata Liu & Chen, sp. nov.; D. vadosulcus Liu & Chen, sp. nov.; D. victoria Liu & Chen, sp. nov. and D. wangi Liu & Chen, sp. nov. Five new combinations are proposed, i.e., D. acron (Nixon, 1967), comb. nov., D. bambusae (Wilkinson, 1928), comb. nov., D. kurosawai (Watanabe, 1940), comb. nov., D. lissos (Nixon, 1967), comb. nov., D. molestae (Muesebeck, 1933), comb. nov. Four newly recorded species are redescribed and illustrated, i.e., D. acron (Nixon, 1967), rec. nov., D. agilis (Ashmead, 1905), rec. nov., D. bambusae (Wilkinson, 1928), rec. nov., and D. ultima (Kotenko, 1986), rec. nov. One species, D. acutituba Song, Chen & Yang, 2006, syn. nov. is synonymized with D. prisca (Nixon, 1967). Fifteen new host are recorded for the following previously described species viz., D. baoris, D. brevicarinata, D. expulse, D. heterusiae, D. hyposidrae, D. kurosawai, D. lacteicolor, and D. prisca and marked by a number sign (#). Eleven new host associations are documented for the following new species: D. alophogaster; D. crassa, D. flexisulcus; D. gleditsia; D. hexagona; D. lincostulata; D. lobesia; D. minuscula; D. multicolor; D. obsolete, and D. rectivena. The hosts of thirty-two species remain unknown. An identification key and distribution maps to the Chinese species of the ultor-group is provided.